2012
DOI: 10.7314/apjcp.2012.13.6.2699
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Proteasome Activator REGγ in Human Laryngeal Carcinoma and Associations with Tumor Suppressor Proteins

Abstract: The functional significance of the proteasome activator REGγ in the regulation of cell proliferation and apoptosis has been recognized. However, pathological contributions to tumor development remain to be elucidated. Both oncogenic proteins and tumor suppressors are targeted by REGγ for proteasomal degradation. It has been proposed that the role of the REGγ in the pathogenesis of cancer is cell-and context-specific. In this study, we aimed to explore the potential involvement of REGγ in laryngeal carcinomas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…REGγ was found to be predominantly localized to the nucleus of EC specimens (Fig. 6A), consistent with published literatures about other cancers [26][27][28][29], but the underlying mechanism of its nuclear-localization remains largely unkown. REGγ was highly expressed in human EC tissues and positively correlated with pathological grade and lymph node metastasis (Supplementary Table S3).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…REGγ was found to be predominantly localized to the nucleus of EC specimens (Fig. 6A), consistent with published literatures about other cancers [26][27][28][29], but the underlying mechanism of its nuclear-localization remains largely unkown. REGγ was highly expressed in human EC tissues and positively correlated with pathological grade and lymph node metastasis (Supplementary Table S3).…”
Section: Discussionsupporting
confidence: 89%
“…REGγ (also called PA28γ, PSME3 or Ki antigen) is a subunit of the 11S activator, which binds and activates the 20S proteasome to degrade specific proteins [21,22], such as cell-cycle inhibitors and SRC-3, in a ubiquitin and ATP-independent manner [23][24][25]. REGγ is reported to be overexpressed in thyroid [26], colorectal [27], breast [28] and laryngeal cancers [29], and is predicted to be associated with multiple oncogenic pathways [30]. The fact that proteasome inhibitors induce apoptosis of EC cells [31] suggests that REGγ-associated proteasome activity plays a role in EC.…”
mentioning
confidence: 99%
“…In addition, PA28 γ overexpression facilitates the growth of laryngeal cancer cells. 25 PA28 γ plays an important role in transformation from oral leukoplakia to oral squamous cell carcinoma. 26 It has been reported that the PA28 γ expression was abnormally high in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits the activity of the tumor suppressor p53 by promoting its nuclear export and mouse double minute 2 homolog (MDM2)-mediated degradation [8,9]. Moreover, PA28γ has been found to be abnormally expressed in colorectal [10], thyroid [11], breast [12], and laryngeal [13] cancers. These results suggest that PA28γ functions as an oncogene.…”
Section: Introductionmentioning
confidence: 99%